Perbedaan Tanda dan Gejala antara Infeksi Dengue Primer dengan Sekunder - Salsabila Adinda Rahman; Wida Purbaningsih; Listya Hanum Siswanti (Bandung Conference Series: Medical Science, 2024)
Abstract. Dengue fever infection is caused by the dengue virus flavivirus (DENV). The dengue fever virus can cause primary infection and secondary infection. Primary infection is the first infection by DENV, while secondary infection is the second infection by DENV which can be determined based on serological examination (IgM and IgG). A literature study was conducted to find out the differences in signs and symptoms between primary and secondary dengue fever infections. Researchers used analytical observational methods with a quantitative approach. The population of this study was 1262 dengue fever infection patients in the inpatient unit at Al-Islam Hospital Bandung City in 2022 and 104 data were taken using a simple random sampling technique. Research sampling used secondary data from medical record data. From the research that has been carried out, it was found that patients with secondary infections had more manifestations of bleeding and hepatomegaly than primary infections. The results show that primary dengue infection is milder than secondary infection. In most cases, primary infection shows symptomatic or mild dengue fever, while secondary infection with a different serotype increases the risk of severe dengue fever (Dengue Hemorrhagic Fever, Dengue Shock Syndrome). Abstrak. Infeksi dengue disebabkan oleh flavivirus dengue virus (DENV). Virus dengue bisa menyebabkan infeksi primer dan infeksi sekunder. Infeksi primer adalah infeksi pertama kali oleh DENV, sedangkan infeksi sekunder adalah infeksi kedua oleh DENV yang dapat ditentukan berdasarkan pemeriksaan serologis (IgM dan IgG). Studi literatur dilaksanakan untuk mencari tentang perbedaan tanda dan gejala antara infeksi dengue primer dengan sekunder. Peneliti menggunakan metode observasional analitik dengan pendekatan kuantitatif. Populasi penelitian ini adalah pasien infeksi dengue unit rawat inap di RS Al-Islam Kota Bandung tahun 2022 yang berjumlah 1262 dan diambil 104 data dengan teknik sampel acak sederhana. Pengambilan sampel penelitian menggunakan data sekunder dari data rekam medis. Dari studi yang telah dilakukan, didapatkan pada pasien infeksi sekunder dengan manifestasi pendarahan dan hepatomegali lebih banyak dibanding infeksi primer. Hasil menunjukkan bahwa infeksi dengue primer lebih ringan dibanding infeksi sekunder. Pada kebanyakan kasus, infeksi primer menunjukan simptomatik atau demam dengue ringan, sedangkan infeksi sekunder dengan serotipe yang berbeda meningkatkan risiko penyakit dengue berat (Demam Berdarah Dengue, Sindrom Syok Dengue).